KEBIJAKAN PERBANKAN SYARI'AH DALAM MENGATASI RISIKO KERUGIAN AKAD MUDHARABAH - Subaidi Subaidi (LP2M Universitas Ibrahimy, 2014)
Mudarabah Bank Shariah has a high risk. Therefore Bank Shariah anticipates it on; 1. Examined the ability of mudarib to manage the business. 2. Clarify the information about the ability of customers funds. 3. Conduct intensively by monitoring and inspection to the customer.BPR Shariah Situbondo takes a policy to solve the risk in mudaraba; first; take persuasively withÂ mudharib to recognize of his debit. Second; legal way by judiciary. Third; take decisive action to sell the collateral which has been agreed upon.But, if there is a damage of the mudaraba, Bank as Shahibul mall does not want to bear the damage, although it is not caused by the negligence of customer/mudharib. Therefore, Islamic law (Bank Sharia) conclude and decide losses damaged in mudaraba is fault/fasid.Â